Samuel Seabury and Charles Inglis: two bishops, two churches - Hebb, Ross N. (Fairleigh Dickinson Univ. Press, 2010)
Introduction -- Origins, early careers, the campaign for Episcopacy, and the revolution -- Episcopal careers -- Seabury and Inglis and the 1662 Book of common prayer -- Polity : emergent and established -- Conclusion -- Appendix I: The Creed of St. Athanasius -- Appendix II: The Colenso Affair -- Appendix III: The Episcopal Church of Scotland